Analysis Of The Causes Of The Scarcity Of 3 Kg LPG Gas Among The People Of Bengkalis Regency - Karmilawati Dwi Rahayu; Ebi Sukma; Fikriyatunnisa; Dika Syahputra (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
National security includes needs that are often used in daily life, especially in household matters which cannot be separated from kitchen needs such as 3 kg LPG gas which is widely used by people whose economic levels are at the lower middle level. However, transportation needs cannot be separated from the availability of fuel supplies used as fuel, but what is currently happening is that there is a scarcity of gas and subsidized fuel in the Bengkalis Regency area. Therefore, this research was conducted to find out the causes of this shortage, so that people's needs can be met properly. This research uses a research method with the type of library research, by examining various data and information which will then be analyzed, so that results are obtained which show that the cause of this shortage is not due to supply, but rather access to crossings for vehicles transporting fuel and kg LPG gas. , this is characterized by an increase in queues which continues to increase significantly. This results in all access being delayed for transport vehicles, as well as public transportation users, because vehicles entering and exiting Bengkalis Island to outside the area can only be accessed from the White Water Roro and Selari River crossing ports.